2021
DOI: 10.1039/d1ra05686g
|View full text |Cite
|
Sign up to set email alerts
|

Journey of anthraquinones as anticancer agents – a systematic review of recent literature

Abstract: Anthraquinones are privileged chemical motifs with diverse therapeutic applications, especially in the treatment of cancer. The extensive literature highlights the significance of anthraquinones as potent anticancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 171 publications
(213 reference statements)
1
52
0
Order By: Relevance
“…Considering the metabolites identified in the leaf and SCC extracts, the results obtained from this study are consistent with other reports of the presence of terpenoid, phenolic, flavonoid, and quinone compounds in R. nasutus leaves, conferring significant free radical scavenging activity and cancer-inhibitory effects [ 41 , 49 , 50 , 56 , 58 , 59 , 83 , 84 ]. Similar metabolite profiles were observed between the leaf and SCC extracts, with the leaf extract potentially showing greater metabolite accumulation.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the metabolites identified in the leaf and SCC extracts, the results obtained from this study are consistent with other reports of the presence of terpenoid, phenolic, flavonoid, and quinone compounds in R. nasutus leaves, conferring significant free radical scavenging activity and cancer-inhibitory effects [ 41 , 49 , 50 , 56 , 58 , 59 , 83 , 84 ]. Similar metabolite profiles were observed between the leaf and SCC extracts, with the leaf extract potentially showing greater metabolite accumulation.…”
Section: Discussionsupporting
confidence: 90%
“…Anthraquinone derivatives, such as doxorubicin and mitoxantrone analogs are potent anticancer drugs owing to their ability to intercalate DNA to induce damage 29 . However, our earlier studies 28 have shown the ability of our lead compound BW-AQ-101 ( Figure 1 ) derived from rhein to down-regulated MDM2 without the general cytotoxicity by inducing DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…Anthraquinones have been recognized as cancer growth inhibitors targeting topoisomerases, telomerase, matrix metalloproteinases, and protein kinase. 29,30 Several drugs containing an anthraquinone scaffold, such as doxorubicin, epirubicin, pixantrone, valrubicin, and MTX, are clinically used to treat various types of cancers. 31 All known telomerase-targeting anthraquinones act as stabilizers of telomeric DNA G4, altering the binding of telomerase enzyme to DNA and blocking telomerase activity in vitro and vivo.…”
Section: Discussionmentioning
confidence: 99%